Legal Aspects of Personal Data Protection in the Digital Era: A Study of Law No. 27 of 2022 - Chairus Suryati; Leni Indrayani (Outline Publisher, 2023)
The development of information technology has had a major impact on the way people interact and manage information, including personal data. In today's digital era, personal data has become a commodity that is vulnerable to misuse if not properly regulated. In response to this, the Indonesian government has passed Law No. 27 of 2022 concerning Personal Data Protection. This Community Service Activity aims to increase public legal awareness of the importance of personal data protection, as well as measure their understanding of the substance of the Law. The activity was carried out through legal counseling, participatory discussions, and pre-tests and post-tests for participants from students and the general public. The results showed a significant increase in legal understanding after the socialization was carried out. In addition, the survey also revealed that the types of digital threats most often experienced by the public are phishing and unauthorized use of data. The level of trust in data management institutions, such as the government and digital platforms, is also still relatively low. This finding emphasizes the importance of ongoing legal education and the active role of the community in maintaining privacy in the digital space. The laws that have been passed are not enough without being followed by legal awareness and strict enforcement of the rules. Therefore, this activity is expected to be the first step in forming a digital culture that is legally aware and protects the rights of citizens as data owners.